PROTOTYPE SMART HOME BERBASIS IOT DENGAN NODEMCU ESP8266, MOTOR SERVO DAN SENSOR SUHU DHT11 BERBASIS WEB - Raharja, Rian Umbara Maulana; Pudoli, Ahmad; Kusumaningsih, Dewi (SKANIKA: Sistem Komputer dan Teknik Informatika, 2022)
Smart home system (Smart home) is a combination of technology and services that are devoted to the home environment with certain functions aimed at increasing the efficiency, comfort, and safety of its residents. A smart home system usually consists of a control and monitoring device for several home devices or appliances that can be accessed via a smartphone. This study designed a control system prototype that is implemented on a smarthome, which is installed with an ESP8266 NodeMCU V3 CH340 microcontroller control device, a Relay Module, 2 LED lights, a 12v DC fan, and a Servo Motor, so that the lights, fans, and servos can be controlled on/off. remotely. The method used in this research is the prototyping method. By using the prototyping method, a prototype system is produced as an intermediary between developers and users so that they can interact in the process of information system development activities. The test results of this prototype all the tools work optimally with internet speeds in the range of 100kb/sec, temperature value updates change every 1-2 seconds, servo motors and lights respond in 1-3 seconds. The results of the Smart Home Prototype System test are concluded that it can provide efficiency in the use of electricity that is controlled remotely, it is safer because notifications are run if the temperature standard is exceeded.